Impact assessment of UNIQLO’s Neighbours Helping Neighbours - NG, Weng Lin (Institutional Knowledge at Singapore Management University, 2025)
The UNIQLO Neighbours Helping Neighbours (NHN) is a pilot programme that redistributes recycled UNIQLO products to those in need. Preloved UNIQLO clothing in good condition are collected, washed and pressed, and then redistributed to partnered social service organisations and family service centres for donation to their core beneficiaries. The objective of the current study is to document and evaluate the impact of the NHN programme on its beneficiaries and present evidence-based recommendations that will aid UNIQLO’s efforts to improve and scale subsequent iterations of this programme. This report will present results obtained from the following data sources: (1) a quantitative survey given to the core beneficiaries of the NHN and (2) qualitative insights collected from both the beneficiaries and the partner organisations of the NHN. This study also explores the need for like-minded stakeholders — organisations, community members, and corporations alike — to come together for the improvement and growth of the NHN programme. The success of this NHN pilot sets the stage for a shift in the clothing industry towards sustainability initiatives that contribute to the re-use of quality clothing for longer wear, as well as circularity of materials while simultaneously providing for those in need in ways that involve local communities.